2003
DOI: 10.1046/j.1365-4362.2003.01862.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of betamethasone valerate foam formulation in comparison with betamethasone dipropionate lotion in the treatment of mild‐to‐moderate alopecia areata: A multicenter, prospective, randomized, controlled, investigator‐blinded trial

Abstract: Betamethasone valerate foam has shown to be an effective and well-tolerated treatment of mild-to-moderate AA. Further trials are warranted to evaluate the role of this new formulation in comparison or in combination with intralesional corticosterioids in AA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 14 publications
0
28
0
3
Order By: Relevance
“…They are thought to work by suppressing the robust autoimmune inflammatory reaction seen in alopecia areata. Betamethasone valerate in a foam vehicle showed increased efficacy in mild-to-moderate alopecia areata versus a lotion vehicle, with 23 of 31 compared with nine of 30 patients showing increased growth of at least 50% [22]. There was no vehicle control.…”
Section: Topical Corticosteroidsmentioning
confidence: 97%
“…They are thought to work by suppressing the robust autoimmune inflammatory reaction seen in alopecia areata. Betamethasone valerate in a foam vehicle showed increased efficacy in mild-to-moderate alopecia areata versus a lotion vehicle, with 23 of 31 compared with nine of 30 patients showing increased growth of at least 50% [22]. There was no vehicle control.…”
Section: Topical Corticosteroidsmentioning
confidence: 97%
“…In another study done by Mancuso G et al, 4 a RGS>3 was observed in 61% of the patients treated with Betamethasone valerate foam. And a RGS>3 was seen in 27% of patients treated with betamethasone dipropionate lotion.…”
Section: Discussionmentioning
confidence: 81%
“…Up to now, numerous studies have been conducted on treatment of alopecia areata and many of those researches have compared the efficacy of different topical agents on hair regrowth (14)(15)(16)(17)(18)(19)(20). In a comparative study of topical 0.05% tretinoin, topical betamethasone dipropionate lotion, and 0.25% dithranol paste, satisfaction was reported by 55% of patients who were treated with topical tretinoin in comparison with 70% and 35% of cases who were respectively underwent topical steroid and dithranol therapy (14).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the combination of 5% minoxidil and 0.5% anthralin was used to treat 51 patients with severe alopecia areata and only 11% of patients achieved cosmetically acceptable hair regrowth (17). In another study, 61% of patients using 0.1% betamethasone vale rate foam showed more than 75% hair regrowth while only 27% of patients who underwent treatment with 0.05% betamethasone dipropionate lotion had the same rate of regrowth (18). Folliculitis is a common side effect of topical corticosteroids; however, telangiectasia and atrophy may rarely develop.…”
Section: Discussionmentioning
confidence: 99%